THE INFLUENCE OF CONSUMER PREFERENCES, PRICE AND QUALITY OF BROILER CHICKEN ON DECISIONS PURCHASE AT RN FARM IN TUMPATAN VILLAGE DELI SERDANG - Bagus Tarfiko Winata; Anggia Sari Lubis; Indra Utama; M. Dani Habra (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
The purpose of this study was to determine and analyze the effect of consumer preferences, price and quality of broiler chicken on purchasing decisions at RN Farm, Tumpatan Village, Deli Serdang. This type of research is quantitative. The population in this study were consumers who made purchases at RN Farm Tumpatan Deli Serdang Village during March, namely 450 consumers. The sample was taken using the Slovin formula, so that the total number of respondents in this study was rounded up to 82 consumers who made purchases at RN Farm, Tumpatan Village, Deli Serdang. Data collection techniques in this study were observation, documentation and questionnaires with a Likert Scale data measurement scale. Data analysis techniques use validity, reliability and classical assumption tests. The data analysis method uses multiple linear regression with the help of the SPSS program. The results of this study partially show that consumer preferences have a positive and significant effect on purchasing decisions. Price has a positive and significant effect on purchasing decisions. The quality of Broiler Chicken has a positive and significant effect on purchasing decisions. Simultaneously, it shows that consumer preferences, price and quality of Broiler Slaughtered Chicken simultaneously influence purchasing decisions at RN Farm, Tumpatan Village, Deli Serdang with an Fcount value (62.359) > Ftabel (2.72), and a significance value of 0.000 <0.05.